PENGEMBANGAN BLOG PEMBELAJARAN MATEMATIKA PADA MATERI PECAHAN DI SEKOLAH MENENGAH PERTAMA - Ignasius Layola Dedy; Dede Suratman; Munaldus Munaldus (UNIVERSITAS TANJUNGPURA, 2021)
This study aims to develop a product for developing a mathematics learning blog on material in junior high school. The research method used in this research is the research and development method. Research and development are the process of developing a new product or improving an existing product. The data collection tools include a material expert validation questionnaire, a media expert validation questionnaire, and a student response questionnaire. From the results of material expert validation, an average score of 75 was obtained with a good category, the results of media expert validation obtained an average score of 75 with a good category, then the response questionnaire was obtained, namely a positive response with a percentage of 96.18% and a negative response with a percentage of 3.82 %. Based on the data obtained, it can be obtained that the blog development product is as expected and in accordance with the needs and curriculum. The responses that have been submitted to students get a very good response.